Research in organizational change and development. - Pasmore, William A.; Woodman, Richard W. (Research in organizational change and development., 2005)
Addressing various topics, challenges, and gaps in our knowledge of organizational change, this book explores the dynamics of time in organizational change, and proposes the use of the concept of ""flow time."" It also examines the issue of excessive change in organizations, which is defined as the simultaneous pursuit of multiple unrelated changes.